A review on reaction mechanisms and catalysts of methanol to olefins process. Issue 12 (2nd December 2022) - Hadi, Naser; Farzi, Ali
Abstract: In this study, different reaction mechanisms and various theories including lumped kinetic models and detailed elementary step reaction mechanisms proposed for methanol to olefins and methanol to propylene (MTO/MTP) processes were comprehensively reviewed. Based on findings and authors' interpretations, the most accurate and reliable reaction mechanisms were introduced. Afterwards, the most applicable catalysts employed for MTO/MTP processes were systematically compared. Various modified catalysts that had been appropriately prepared for enhancing the catalytic activity, increasing of light olefins selectivity and prolonging catalytic life-time were completely overviewed. Furthermore, the role of template materials in the performance of synthesized zeolite catalysts was completely investigated and their effects on morphology, catalytic activity and catalytic stability of provided samples were thoroughly discussed. The authors hope that the current review gives a deeper view for the investigations of MTO/MTP processes.